2017
DOI: 10.1128/jvi.02477-16
|View full text |Cite
|
Sign up to set email alerts
|

HIV Controllers Exhibit Enhanced Frequencies of Major Histocompatibility Complex Class II Tetramer+Gag-Specific CD4+T Cells in Chronic Clade C HIV-1 Infection

Abstract: Immune control of viral infections is heavily dependent on helper CD4 T cell function. However, the understanding of the contribution of HIV-specific CD4 T cell responses to immune protection against HIV-1, particularly in clade C infection, remains incomplete. Recently, major histocompatibility complex (MHC) class II tetramers have emerged as a powerful tool for interrogating antigen-specific CD4 T cells without relying on effector functions. Here, we defined the MHC class II alleles for immunodominant Gag CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
(55 reference statements)
0
24
0
Order By: Relevance
“…Tfh). Human HLA class II diversity is a tremendous challenge in the development of broadly applicable reagents, but recent efforts to develop suites of HLA class II tetramers for chronic infections such as HIV, HCV and tuberculosis have allowed an increased understanding of human CD4 + T cell differentiation during chronic infections 82,83 . However, even tetramers can introduce a bias, given that they can only identify responses to a single epitope (Figure 2).…”
Section: Cd4+ T Cells In Human and Non-human Primate Chronic Viral Inmentioning
confidence: 99%
“…Tfh). Human HLA class II diversity is a tremendous challenge in the development of broadly applicable reagents, but recent efforts to develop suites of HLA class II tetramers for chronic infections such as HIV, HCV and tuberculosis have allowed an increased understanding of human CD4 + T cell differentiation during chronic infections 82,83 . However, even tetramers can introduce a bias, given that they can only identify responses to a single epitope (Figure 2).…”
Section: Cd4+ T Cells In Human and Non-human Primate Chronic Viral Inmentioning
confidence: 99%
“…Figure 5A shows representative flow plots of unstimulated controls (top panel), cytokine secreting antigen specific CD4 + cells responding to HIV peptide pools (middle panel) or SEB stimulation (bottom panel) in an ICS assay. Our group previously showed that most of the HIV-specific CD4 + T cells in chronic clade C infection target the HIV Gag protein (26). Here we found no significant differences in Gag, Nef and Env responses (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have implicated bulk CD4 + T cells in immune mediated control of chronic HIV infection (25, 26, 33), but little is known about the role of HIV-specific cTfh cells in HIV control mainly because of their very low frequency in circulation and the paucity of reliable tools to study them. Even though there were few numbers of cytokine secreting cTfh cells in response to stimulation by HIV peptide as previously shown (34), our tetramer staining results provided conclusive evidence of the existence of HIV-specific cTfh cells during primary HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The Gag293 peptide and its shorter variants are able to bind efficiently to an unusually large array of HLA-DR molecules, with up to 13 alleles recognized (43, 44). This promiscuous HLA II binding likely contributes the frequent detection of the Gag293-specific response, which is the most immunodominant among CD4 responses directed at the HIV proteome (11, 24, 43, 44). HLA cross-restriction also depends on TCR clonotype properties, as by definition an HLA-cross-restricted TCR can recognize multiple peptide/MHC complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the high degree of clonotype sharing observed in controller CD4+ T cells opens the possibility to search for these clonotypes in a diverse population of vaccinated volunteers. We focused the clonotypic analysis on Gag293 specific cells, as this epitope is remarkably immunodominant, independently of the MHC II background (11, 23, 24). In addition, the Gag293 epitope is located in the most conserved region of HIV-1 capsid, called the major homology region, and is thus rarely mutated, with two cases of mutational escape in minor viral variants reported so far (25, 26).…”
Section: Introductionmentioning
confidence: 99%